Del apogeo "lulista" a la destitución de Dilma : el devenir popular neodesarrollista en Brasil - Merino, Gabriel Esteban (2018)
El presente trabajo analiza la articulación político-social y el esquema de poder gobernante en Brasil durante los gobiernos del PT. Se estudia cómo la articulación nacional popular neodesarrollista encabezada por el liderazgo de "Lula" tendrá una influencia decisiva en el Estado, en un contexto internacional favorable. Por otro lado, se pretende observar la crisis de la articulación lulista y caída del gobierno del PT, especialmente en relación a dos puntos de inflexión fundamentales: la modificación del escenario internacional, y la agudización de las contradicciones de la articulación nacional-popular neodesarrollista, en el marco de los límites de la dependencia
This paper analyzes the political-social articulation and the regime of governing power in Brazil during the PT governments. It is studied how the neodesarrollista popular national articulation headed by the leadership of "Lula" will have a decisive influence in the State, in a favorable international context - increasing relative multipolarity, high prices of the commodities and advance of autonomous regionalism in the region. From there, a set of measures and geostrategic positions can be explained. On the other hand, it is intended to observe the crisis of the articulation of Lula and the fall of the PT government, especially in relation to two fundamental inflection points: a) The modification of the international scenario and the pressure of the dominant forces in the United States and in the "Global North" in relation to Brazil's foreign policy, and b) the aggravation of the contradictions of both the power scheme in the government and within the neodesarrollista national-popular articulation, in the framework of the corruption scandal and the limits of the dependence
Keywords: Lulismo; Articulación político-social; Neodesarrollismo; Nacionalismo popular; Dependencia; Lulism; Political-social articulation; Neodesarrollismo; Popular nationalism; Dependence; Gobierno; Lula da Silva, Luiz Inácio; Rousseff, Dilma; Brasil